Building Motivation and Entrepreneurial Spirit for MSMEs in the Tenggilis Mejoyo Village, Surabaya - Suhermin, Suhermin; Ramadhani, Yesa Cahayaning; Budiyanto, Budiyanto; Subardjo, Anang (Trescode Green Organization, 2023)
The purpose of this activity is to increase the motivation and spirit of UMKM Actors of Renggilis Mejoyo Village, Surabaya. Participants in this activity amounted to 30 MSME actors. Analysis of the results of the evaluation of activities is carried out with descriptive statistics. The results of the analysis show that the SMEs are aware of or understand that there must be a very diverse form of motivation, not only in the form of words, but motivation can also be in the form of a strong desire and encouragement from within itself. This motivation is given to SMEs to review motivation and group them into several forms from time to time. Hope in the future food and beverage products from UKM Kelurahan Tenggilis City of Surabaya can reach national markets and cannot reach the international market.